Policing rape: the way forward - Hohl, Katrin (Routledge frontiers of criminal justice, 2024)
"The policing of rape is in permacrisis. This book addresses the question of why police investigations continue to fail most rape victim-survivors and puts forward a framework for what policing can do to change this. Low conviction rates and poor victim-survivor experiences are the hallmarks of the rape justice gap. Three decades of research, policy and legal changes have tweaked rape investigations to alleviate some of their ills, however, for the majority of victim-survivors, the process remains grueling. Police forces are notoriously resistant to reform, even in the face of rapidly declining public trust. The starting point of this book is the recognition that if we want profound change in policing, we must try something new. To do so, the authors move from asking 'What is it about rape that makes it so difficult for police to investigate it well?' to asking 'What is it about the police that makes it so difficult for police to investigate rape well?'. Policing Rape sets out a practice-oriented theoretical framework for radically and sustainably transforming rape investigations, rape prevention, and the quality of officer engagement with victim-survivors. The authors reflect on the journey of putting this framework into practice within Operation Soteria Bluestone as a step on the path towards a radical transformation of rape policing. This book is essential reading for all those looking to understand and improve the policing of rape"--